A novel selective laser melting process for glass fiber-reinforced metal matrix composites. (October 2018) - Samanta, Avik; Wang, Qinghua; Ding, Hongtao
Abstract: A novel selective laser melting (SLM) process is presented for fabrication of glass fiber-reinforced metal (GFRM) matrix composite material. The SLM experiments are conducted using aluminum powders as matrix material and S-2 glass fibers as reinforcement. Laser heating turns the aluminum powders into a molten viscous flow which encapsulates the S-2 glass fibers. The glass fibers are not melted during the SLM process as the glass transition temperature is significantly higher than the melting point of aluminum powder. After the process, a mechanically enhanced glass fiber-reinforced metal matrix composite is produced with intact glass fibers embedded in the aluminum matrix.